Hindered diffusion of MRI contrast agents in rat brain extracellular micro‐environment assessed by acquisition of dynamic T1 and T2 maps. (29th October 2012) - Marty, B.; Djemaï, B.; Robic, C.; Port, M.; Robert, P.; Valette, J.; Boumezbeur, F.; Le Bihan, D.; Lethimonnier, F.; Mériaux, S.
<x xml:space="preserve">Abstract</x> The knowledge of brain tissues characteristics (such as extracellular space and tortuosity) represents valuable information for the design of optimal MR probes for specific biomarkers targeting. This work proposes a methodology based on dynamic acquisition of relaxation time maps to quantify in vivo MRI contrast agent concentration after intra‐cerebral injection in rat brain. It was applied to estimate the hindered diffusion in brain tissues of five contrast agents with different hydrodynamic diameters (Dotarem® ≈ 1 nm, P846 ≈ 4 nm, P792 ≈ 7 nm, P904 ≈ 22 nm and Gd‐based emulsion ≈ 170 nm). In vivo apparent diffusion coefficients were compared with those estimated in an obstacle‐free medium to determine brain extracellular space and tortuosity. At a 2 h imaging timescale, all contrast agents except the Gd‐based emulsion exhibited significant diffusion through brain tissues, with characteristic times compatible with MR molecular imaging (<70 min to diffuse between two capillaries). In conclusion, our experiments indicate that MRI contrast agents with sizes up to 22 nm can be used to perform molecular imaging on intra‐cerebral biomarkers. Our quantification methodology allows a precise estimation of apparent diffusion coefficients, which is helpful to calibrate optimal timing between contrast agent injection and MRI observation for molecular imaging studies. Copyright © 2012 John Wiley & Sons, Ltd.